2012
DOI: 10.4142/jvs.2012.13.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Biceps femoris muscle transposition for treatment of cranial cruciate ligament rupture in small breed dogs

Abstract: The purpose of this study was to evaluate a new extracapsular surgical technique for the treatment of cranial cruciate ligament rupture in small breed dogs. Nine small breed dogs (seven females and two males) weighing ≤ 15 kg were treated with biceps femoris muscle transposition (BFT). The duration of the BFT procedure was 20 min. Each patient underwent a standard clinical protocol and a questionnaire for the owners. Follow-up (at 1, 3, and 12 months postoperative) confirmed significant improvement in all pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…We found that 7.1% of dogs with CCL disease admitted to our clinic were small breed dogs, consistent with previous observations that CCL disease is an important cause of lameness in small breed dogs . Bilateral CCL disease was identified in 38.1% of small breed dogs compared with 9.8% of medium and large breed dogs, which may suggest a difference in the rate of occurrence of CCL rupture in small breed dogs, or that small breed dogs tolerate unilateral lameness relatively well and are presented for surgery only when lameness becomes bilateral.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that 7.1% of dogs with CCL disease admitted to our clinic were small breed dogs, consistent with previous observations that CCL disease is an important cause of lameness in small breed dogs . Bilateral CCL disease was identified in 38.1% of small breed dogs compared with 9.8% of medium and large breed dogs, which may suggest a difference in the rate of occurrence of CCL rupture in small breed dogs, or that small breed dogs tolerate unilateral lameness relatively well and are presented for surgery only when lameness becomes bilateral.…”
Section: Discussionsupporting
confidence: 90%
“…One study of small breed dogs with CCL disease noted a lower incidence of meniscal injuries compared to larger dogs . The low incidence of meniscal disease in small breed dogs was given as a reason to avoid arthrotomy in a report discussing management of CCL disease in small breed dogs . Four stifles (13.8%, stifles 5, 14, 21, and 22) in our study had meniscal disease, which corresponds with previous ranges of 10–70% in larger breed dogs .…”
Section: Discussionsupporting
confidence: 84%
“…6 using the same method. Tatarunas et al (2006) used a graduation method similar to the one used in our experiment and obtained similar values in the preoperative assessment. Tamburro et al (2012), using an extra-articular technique, obtained satisfactory results from one month postoperative, with an average of two months for the normal limb function after the surgical procedure.…”
Section: Discussionmentioning
confidence: 89%
“…The average radiographic degenerative lesion of these animals was 123 days. Several studies have shown that the instability generated by the CCrL lesion leads to joint degeneration with radiographic signs in 70 to 90% of the animals (SELMI et al, 2002;TATARUNAS et al, 2006). These data show that osteoarthritis induced by CCrLR is severe and rapidly evolving, unlike in humans with knee ligament lesion.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation